2001
DOI: 10.1016/s0005-2728(00)00261-9
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ischemic inhibition of F1F0-ATPase in rat and human myocardium

Abstract: The physiological role of F(1)F(0)-ATPase inhibition in ischemia may be to retard ATP depletion although views of the significance of IF(1) are at variance. We corroborate here a method for measuring the ex vivo activity of F(1)F(0)-ATPase in perfused rat heart and show that observation of ischemic F(1)F(0)-ATPase inhibition in rat heart is critically dependent on the sample preparation and assay conditions, and that the methods can be applied to assay the ischemic and reperfused human heart during coronary by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…As it was previously demonstrated by several authors (Corbucci, 2000;Ylitalo et al, 2001;Marin-Garcia and Goldenthal, 2002), our results clearly show that oxidative phosphorylation is very sensitive to ischemia, which dramatically affects mitochondrial respiratory chain (Fig. 1), as it can be shown by the decrease in the respiratory control ratio [that is, the ratio between the oxygen consumption during active phosphorylation (state 3) and after active phosphorylation (state 4)], when compared to the value obtained in mitochondria from the control group (2.71 T 0.42 versus 1.51 T 0.13; P = 0.0002).…”
Section: Resultssupporting
confidence: 73%
“…As it was previously demonstrated by several authors (Corbucci, 2000;Ylitalo et al, 2001;Marin-Garcia and Goldenthal, 2002), our results clearly show that oxidative phosphorylation is very sensitive to ischemia, which dramatically affects mitochondrial respiratory chain (Fig. 1), as it can be shown by the decrease in the respiratory control ratio [that is, the ratio between the oxygen consumption during active phosphorylation (state 3) and after active phosphorylation (state 4)], when compared to the value obtained in mitochondria from the control group (2.71 T 0.42 versus 1.51 T 0.13; P = 0.0002).…”
Section: Resultssupporting
confidence: 73%
“…Oligomycin, a potent inhibitor of mitochondrial F 1 F 0 -ATPase, has long been used to inhibit state 3 respiration in isolated mitochondria (27). However, recent observations by Ylitalo et al (28) showed that the concentration of oligomycin required for 50% inhibition of the mitochondrial F 1 F 0 -ATPase was fivefold lower than its concentration required for 50% inhibition of electron flux through the respiratory chain, and hence, oxygen consumption. This leaves open a window of oligomycin concentrations at which intracellular AMP is elevated while simultaneously oxygen consumption is not inhibited.…”
Section: Resultsmentioning
confidence: 92%
“…The drop in intracellular ATP acts synergistically, because the AMP-driven activation is inhibited by high ATP, making the AMP/ATP ratio the major determinant of AMP kinase activation (27,28). However, this study requires the inhibition of mitochondrial ATP production, while at the same time aerobic metabolism is not inhibited.…”
Section: Resultsmentioning
confidence: 98%
“…Because of the tight coupling between FA oxidation and FA uptake, oligomycin would be expected to reduce FA uptake under these anaerobic conditions rather than to stimulate it. However, a recent study has demonstrated that the concentration of oligomycin required for 50% inhibition (IC 50 ) of the mitochondrial F 1 F 0 -ATPase is fivefold lower than its IC 50 for inhibition of electron flux through the respiratory chain [130]. This discrepancy opens a window of oligomycin concentrations at which the [74].…”
Section: Regulation By Contractionmentioning
confidence: 99%